Synthesis, electronic transport and optical properties of Si:α-Fe2O3 single crystals. Issue 3 (23rd December 2015) - Rettie, Alexander J. E.; Chemelewski, William D.; Wygant, Bryan R.; Lindemuth, Jeffrey; Lin, Jung-Fu; Eisenberg, David; Brauer, Carolyn S.; Johnson, Timothy J.; Beiswenger, Toya N.; Ash, Richard D.; Li, Xiang; Zhou, Jianshi; et al.
Abstract : We report the synthesis of silicon-doped hematite (Si:α-Fe2 O3 ) single crystals via chemical vapor transport, with Si incorporation on the order of 10 19 cm −3 . Abstract : We report the synthesis of silicon-doped hematite (Si:α-Fe2 O3 ) single crystals via chemical vapor transport, with Si incorporation on the order of 10 19 cm −3 . The conductivity, Seebeck and Hall effect were measured in the basal plane between 200 and 400 K. Distinct differences in electron transport were observed above and below the magnetic transition temperature of hematite at ∼265 K (the Morin transition, T M ). Above 265 K, transport was found to agree with the adiabatic small-polaron model, the conductivity was characterized by an activation energy of ∼100 meV and the Hall effect was dominated by the weak ferromagnetism of the material. A room temperature electron drift mobility of ∼10 −2 cm 2 V −1 s −1 was estimated. Below T M, the activation energy increased to ∼160 meV and a conventional Hall coefficient could be determined. In this regime, the Hall coefficient was negative and the corresponding Hall mobility was temperature-independent with a value of ∼10 −1 cm 2 V −1 s −1 . Seebeck coefficient measurements indicated that the silicon donors were fully ionized in the temperature range studied. Finally, we observed a broad infrared absorption upon doping and tentatively assign the feature at ∼0.8 eV to photon-assisted small-polaron hops. These results are discussed in the context of existing hematite transport studies.